İmam İbrahim B. Said El-Cevherî’nin Hayatı ve Hadis İlmindeki Yeri - Yazıcı, Emre (Fatih Sultan Mehmet Vakıf Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2022)
Başta kütüb-i sitte olmak üzere temel hadis kaynaklarının yazıldığı hicri III. asır hadis tarihinin en önemli dönemlerindendir. Aslında bu kaynaklar büyük oranda bir önceki asırda tedvin edilen hadis eserlerinden nakillerle meydana getirilmiştir. Dolayısıyla III. asrın temel hadis kaynaklarını kaleme alan kütüb-i sitte müellifleri ve diğer muhaddislerin hocalarının ve bu hocaların eserlerinin bilinmesi hadis tarihi açısından büyük önem arz etmektedir. Hicrî III.asır muhaddislerinden İmam İbrahim b. Saîd el-Cevherî, başta Veki’ b.Cerrâh, Süfyan b. Uyeyne, Yahya b. Maîn gibi hadis imamları olmak üzere birçokalimden ders almış ve daha sonra içlerinde kütüb-i sitte imamlarının da olduğu birçok hadis alimine hocalık yapmıştır. Aynı zamanda bir Müsned de telif eden Cevheri’nin bu eseri maalesef günümüze ulaşmamıştır. Bu çalışmada, hicrî III.asır muhaddisleri arasında önemli bir yeri olan İbrahim b.Saîd el-Cevherî’nin hadis ilmindeki yeri ve Kütüb-i sittedeki rivayetleri tek tek elealınmıştır. Ayrıca el-Cevheri’nin kayıp olan Müsned adlı eseri hakkında kaynaklardaki bilgiler ve rivayetler üzerinden bir tasavvur oluşturmaya çalışılmıştır.

The third century of Hijri, in which the main hadith sources, especially the al-Qutub al-Sitte, were written, is one of the most important periods in the history of hadith. In fact, these sources were largely composed of transmissions from the hadith works that had been edited in the previous century. Therefore, it is of great importance in terms of the history of hadith to know the teachers of the authors of the al-Qutub al-Sitta and other muhaddithis who wrote the basic hadith sources of the third century and their works. Ibrahim b. Saīd al-Jawharī, one of the muhaddiths of the third century, received knowledge from many scholars, especially hadith imams such as Waqi' b. Jarrah, Sufyan b. Uyayna, Yahya b. Maīn, and later became a teacher to many hadith scholars, including the imams of the books of hadith. The third century of Hijri, in which the main hadith sources, especially the al-Qutub al-Sitte (famous six books of hadith), were written, is one of the most important periods in the history of hadith. In fact, these sources were largely composed of transmissions from the hadith works that had been edited in the previous century. Therefore, it is of great importance in terms of the history of hadith to know the teachers of the authors of the al-Qutub al-Sitta and other muhaddithis who wrote the basic hadith sources of the third century and their works. Ibrahim b. Saīd al-Jawharī, one of the muhaddithis of the third century, received knowledge from many scholars, especially hadith imams such as al-Waqi' b. Jarrah, Sufyan b. Uyayna, Yahya b. Maīn, and later became a teacher to many hadith scholars, including the imams of the books of hadith. Unfortunately, this work of Jawhari, who also wrote a Musnad, has not survived to the present day. In this study, the place of an important muhaddith called Ibrahim b. Saīd al-Jawhari and his narrations in the al-Qutub as- Sitte are discussed one by one. In addition, an attempt has been made to create a conception about al-Jawhari's lost work called Musnad through the information and narrations in the sources.
Imam Ibrahim B. Said Al-Jawhary His Life and Place in Hadith Literature
Keywords: Cevherî; Müsned; Hadis; Râvî; Kütüb-i Sitte; Al-Jawhari; Musnad; Hadith; Narrator; Al-Qutub As-Sitta